Adaptações cardiorrespiratórias e neuromotoras ao uso de exergames em crianças participantes de aulas de educação física - Bezerra, Madson Rodrigo Silva (2018)
Introduction: Exergames appear as an excellent way for the change of sedentary behavior and source of regular physical activity practice in children and adolescents. Objective: To verify the effectiveness of exergames in physical education classes to provide cardiorespiratory, neuromotors and flexibility changes in children. Methods: 59 schoolchildren aged 8 to 10 years, divided into two groups, were randomly assigned to CG (n = 30) and EG (n = 29). The results were shown in two manuscripts. In the first one, the cardiorespiratory response was observed in 16 sessions with the use of exergames. In the second study, the neuromotor responses were observed. In both manuscripts the statistical analysis was made from factorial ANOVA 2x2, with effect size and p <0.05. In all analyzes, SPSS for Windows, version 23.0 was used. Results: The first manuscript identified significant increase in students who practiced exergames in physical education classes, F (1, 30) = 13,236; p <0.05; r = 0.54 In addition, the control group did not show significant change during the intervention time F (1.30) = 0.32; p = 0.57; r = 0.10 and in the comparison between the groups there was a significant difference in cardiorespiratory adaptation F (1, 33) = 6.27; p <0.05; r = 0.41. The second manuscript identified when analyzing the level of flexibility between the groups, significant changes, F (1,30) = 7,683; p <0.01; r = 0.45 and presented a significant change in GE F (1.30) = 15.1; p <0.01; r = 0.57 and showed no significant changes in GC F (1.30) = 0.52; p = 0.47; r = 0.13. In the variable Strength of upper limbs only showed significant adaptation in the GE F (1.30) = 5.01; p <0.05; r = 0.37, showed no significant changes in CG and between groups. In the abdominal strength variable, there were no significant changes. Conclusion: the use of exergames in physical education classes promoted significant adaptations in the cardiorespiratory variable. In the same way that it promoted significant adaptations in the levels of flexibility and strength of upper limbs in its practitioners, but did not significantly alter the abdominal strength variable.